Practical Fashion Tech Wearable Technologies for Costuming, Cosplay, and Everyday - Horvath, Joan; Hoge, Lyn; Cameron, Rich (Apress : Imprint: Apress, 2016)
Practical Fashion Tech is the result of a collaboration between two technologists and a veteran teacher, costumer, and choreographer. They came together to pull back the curtain on making fun and innovative costumes and accessories incorporating technologies like low-cost microprocessors, sensors and programmable LEDs. Fashion tech can require skills in design, pattern-making, sewing, electronics, programming, and 3D printing. Besides the tech skills, making a good costume or accessory also requires knowledge of the intangibles of what makes a good costume. Regardless of whether you are coming at this from the theater costuming, sewing, or electronics side, this book will help you get started with the other skills you need. More than just a book of projects (although it has those too), Practical Fashion Tech teaches why things are done a certain way to impart the authors' collective wealth of experience. Whether you need a book for a wearable tech class or you just want to get started making fantastic costumes and wearables on your own, Practical Fashion Tech will get you there.